The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.optcom.2009.06.033
|View full text |Cite|
|
Sign up to set email alerts
|

Numerical representation of quantum states in the positive-P and Wigner representations

Abstract: Numerical stochastic integration is a powerful tool for the investigation of quantum dynamics in interacting many body systems. As with all numerical integration of differential equations, the initial conditions of the system being investigated must be specified. With application to quantum optics in mind, we show how various commonly considered quantum states can be numerically simulated by the use of widely available Gaussian and uniform random number generators. We note that the same methods can also be app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 49 publications
0
99
0
2
Order By: Relevance
“…The truncated Wigner equations are solved numerically by taking averages over a large number of stochastic trajectories, with initial conditions sampled probabilistically [12,19].…”
Section: Physical Model Hamiltonian and Equations Of Motionmentioning
confidence: 99%
“…The truncated Wigner equations are solved numerically by taking averages over a large number of stochastic trajectories, with initial conditions sampled probabilistically [12,19].…”
Section: Physical Model Hamiltonian and Equations Of Motionmentioning
confidence: 99%
“…In Refs. [25,26] Olsen et al demonstrated explicitly that sampling of W |n (α) indeed produced all moments |α| m W of the exact Wigner distribution up to O(1/n 2 ) relative to the leading order, implying that the contribution of all but the final oscillation in W |n (α) can be considered approximately negligible. In light of this, one could also regardW |n (α), Eq.…”
Section: Formal Derivationmentioning
confidence: 99%
“…The latter can, for instance, represent coherent, thermal, squeezed or Fock states [43] and its time evolution is governed by classical trajectories evolving according to Eqs. (11).…”
Section: B the Initial Statementioning
confidence: 99%